Biomechanical Evaluation of Decellularized and Crosslinked Corneal Implants Manufactured From Porcine Corneas as a Treatment Option for Advanced Keratoconus - Wilson, Abby; Jones, John; Marshall, John (Frontiers in Bioengineering and Biotechnology, 2022)
Currently corneal transplantation is the main treatment for late-stage keratoconus; however, transplantation procedures are accompanied by significant risk of post-surgical complications; this in addition to supply limitations imposed by a worldwide shortage of human donor corneas, has driven the development of alternative therapies. One such therapy is the use of corneal implants derived from porcine corneas (Xenia®, Gebauer Medizintechnik GmbH, Neuhausen, DE). In contrast to human donor tissue, these implants can be produced on demand and due to the processes used pose no risks for host-immune rejection. Their use has already been demonstrated clinically in patients for preventing the progression of topographic changes in keratoconus whilst improving visual acuity. The implants are derived from natural tissue and not standardised synthetic material, whilst this likely reduces the risk of issues with bio-incompatibility, there is inevitably variability in their intrinsic mechanical properties which requires investigation. Here, speckle interferometry is employed to examine the biomechanical properties, in response to physiologically representative forces, of native porcine corneal tissue prior to processing and after a proprietary 4-stage process involving decellularization, washing, compression and crosslinking. The control lenticules had an average Young’s modulus (E) of 11.11 MPa (range 8.39 – 13.41 MPa), following processing average E of the lenticules increased by 127 % over that of the unprocessed tissue to 25.23 MPa (range 18.32 – 32.9 MPa). The variability in E of the lenticules increased significantly after processing suggesting variability in the propensity of the native tissue to processing. In summary, it is possible to produce thin (< 90 µm) lenticules from porcine corneas with enhanced stiffness that are effective for treating late-stage keratoconus. Due to the observed variability in the responses of lenticules to processing, interferometry could be a useful technique for ensuring quality control in commercial production via biomechanical screening.